The determination of the weld dimension with diameter of the electrode wire 2 mm - Palić, Vlastimir (Journal of Production Engineering, 2023)
In this paper, the influence of changes in welding current and voltage on arc penetration depth, the distance between the toes of the weld, and weld reinforcement has been investigated. The welds were created using automatic submerged arc welding with a 2 mm electrode wire diameter, and domestic welding materials were used.